Effects of chronic oral treatment with aripiprazole on the expression of NMDA receptor subunits and binding sites in rat brain - Segnitz, Nina; Ferbert, Thomas; Schmitt, Andrea; Gass, Peter; Gebicke-Härter, Peter J.; Zink, Mathias (Psychopharmacology, 2011)
The glutamatergic theory of schizophrenia proposes a dysfunction of ionotropic N-methyl-d-aspartate receptors (NMDA-R). Several therapeutic strategies address NMDA-R function and the effects of antipsychotic agents on NMDA-R expression have been described. Within the second-generation antipsychotics, the partial dopaminergic and serotonergic agonist aripiprazole (APZ) was able to counteract the behavioral effects of NMDA-R antagonists.